Construction of a 30kW SOFC Gas Turbine Hybrid Power Plant. (2nd June 2015) - Henke, Moritz; Steilen, Mike; Schnegelberger, Christian; Riedel, Marc; Hohloch, Martina; Bücheler, Sandro; Herbst, Melanie; Huber, Andreas; Kallo, Josef; Friedrich, K. Andreas
Abstract : Hybrid power plants consisting of SOFC and gas turbine promise high electrical efficiencies. The German Aerospace Center aims to build and operate such a hybrid power plant with an electrical power output of 30 kW. The presentation will illustrate the general concept of the power plant and give an overview of the current status of the project.